PENGARUH KEPEMILIKAN KELUARGA DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK DENGAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR - Anggu Batari Mulyadi; Muh Su’un; Ratna Sari (Jurnal Riset Perpajakan: Amnesty, 2021)
This study aims to obtain empirical evidence on the influence of family ownership variables and firm size on tax avoidance and the influence of independent commissioners variables as a moderating variable in the influence of family ownership and firm size on tax aggressiveness. Samples in this study amounted to 13 manufacturing companies on The Indonesia Stock Exchange in 2017 – 2019. Test used Regression Analysis and Moderated Regression Analysis. The results of this study indicate that company ownership has no effect on tax aggressiveness and firm size has positive effect on tax aggressiveness. This study also shows that independent commissioners interaction is not able to moderate (weakens) the influence of family ownership on tax aggressiveness. Independent commissioners is able to moderate (weakens) the influence of firm size on tax aggressiveness.